RANS and LES Simulations of Localized Pollutant Dispersion Around High-Rise Buildings Under Varying Temperature Stratifications - Jinrong Zhao; Dongpeng Guo; Zhehai Zhang; Jiayi Guo; Yunpeng Li; Junfang Zhang; Xiaofan Wang (Atmosphere, 2025)
This research investigates the influence of buildings on the flow pattern and pollutant spread under different temperature stratification scenarios. Using Reynolds-averaged Navier–Stokes (RANS) equations alongside the large eddy simulation (LES) model, the findings were validated through comparisons with wind tunnel experiments. Results indicate that the return zone length on the leeward side of the building is the longest, around 1.75 times the building height (H) when the Richardson number (Rib) is 0.08. This return zone length reduces to approximately 1.4 H when Rib is 0.0 and further decreases to 1.25 H with a Rib of −0.1. Pollutant dispersion is similarly affected by the flow field, which aligns with these trends. The studied models revealed that LES proved the most accurate, closely matching wind tunnel results across all temperature stratification levels, while RANS overestimated values at building height (z/H = 1.0) and around the building (x/H < 0.625). To balance computational efficiency with prediction accuracy, a hybrid method integrating LES and RANS is recommended.